(untitled) (Global Journal of Medical Research, 2016)
The article presents the case of a 40-year old patient, diagnosed with partial epileptic seizures since he was one year old. He also presented a psychomotor delay and spastic left palsy. For a long time, the diagnosis was infant encephalopathy. In 2014, during an MRI investigation, a large, right-side, pseudo-tumoral, temporo-parietal heterothopia was found. This heterothopia also presented a posterior agenesis of the corpus callosum. The grey matter focal heterothopia explained the cause of the epileptic seizures.